Effects of phosphonium‐based ionic liquids on the lipase activity evaluated by experimental results and molecular docking. (23rd April 2019) - Barbosa, Milson S.; Freire, Cintia C. C.; Souza, Ranyere L.; Cabrera‐Padilla, Rebeca Y.; Pereira, Matheus M.; Freire, Mara G.; Lima, Álvaro S.; Soares, Cleide M. F.
Abstract: In this work, the effect of several phosphonium‐based ionic liquids (ILs) on the activity of lipase from Burkholderia cepacia (BCL) was evaluated by experimental assays and molecular docking. ILs comprising different cations ([P4444 ] +, [P444(14) ] +, [P666(14) ] + ) and anions (Cl −, Br −, [Deca] −, [Phosp] −, [NTf2 ] − ) were investigated to appraise the individual roles of IL ions on the BCL activity. From the activity assays, it was found that an increase in the cation alkyl chain length leads to a decrease on the BCL enzymatic activity. ILs with the anions [Phosp] − and [NTf2 ] − increase the BCL activity, while the remaining [P666(14) ]‐based ILs with the Cl −, Br −, and [Deca] − anions display a negative effect on the BCL activity. The highest activity of BCL was identified with the IL [P666(14) ][NTf2 ] (increase in the enzymatic activity of BCL by 61% at 0.055 mol·L −1 ). According to the interactions determined by molecular docking, IL cations preferentially interact with the Leu17 residue (amino acid present in the BCL oxyanion hole). The anion [Deca] − has a higher binding affinity compared to Cl − and Br −, and mainly interacts by hydrogen‐bonding with Ser87, an amino acid residue which constitutes the catalytic triad of BCL. The anions [Phosp] − and [NTf2 ] − have high binding energies (−6.2 and −5.6 kcal·mol −1, respectively) with BCL, and preferentially interact with the side chain amino acids of the enzyme and not with residues of the active site. Furthermore, FTIR analysis of the protein secondary structure show that ILs that lead to a decrease on the α‐helix content result in a higher BCL activity, which may be derived from an easier access of the substrate to the BCL active site.